TINGKAT KERUSAKAN HUTAN MANGROVE PANTAI DI DESA MALAKOSA KECAMATAN BALINGGI KABUPATEN PARIGI MOUTONG - Anugra, Fuad; Umar, Husain; Toknok, Bau (Warta Rimba, 2014)
The main cause of mangrove destruction was due to land convertion to housing, aquaculture, illegal loging. Those uncontroled activities was neglect to consider the environmental preservation. Malakosa is one of the village which has mangrove forest, however most of the forest was declining in number, it is therefore important research on the extent of damage to be done in orderto manage the mangrove forest. This phenomenon had motivated this research to investigate the extend and the caused of mangrove forest destruction in Malakosa village, Balinggi district, Parigi Moutong Regency. This research employ Nested Sampling Method. Data was collected from three path. These includes path 1 at second floodgate, path 2 at first floodgate, and path 3 at third floodgate. Physic and water chemical parameter observations was also conducted at these three different floodgates. The result shows that the extend of mangrove forest destruction at malakosa village is between good to severe range continum, with density rate of 6700 btg/ha (low destruction), 1300 btg/ha (modest destruction), and 100 btg/ha (high destruction). Although the physic and water chemical effects on observation stations was still in good conditions, the salinity parameter and iron (Fe) parameters was found to be above the accepted standard.Keyword: Destruction, Forest, Mangrove